Making CAR T Cells a Solid Option for Solid Tumors - Schmidts, Andrea; Maus, Marcela V. (Frontiers in Immunology, 2018)
Adoptive cell therapy with chimeric antigen receptor (CAR) T cells aims to redirect the patient’s own immune system to selectively attack cancer cells. To do so, CAR T cells are endowed with specific antigen recognition moieties fused to signaling and costimulatory domains. While this approach has shown great success for the treatment of B cell malignancies, response rates among patients with solid cancers are less favorable. The major challenges for CAR T cell immunotherapy in solid cancers are the identification of unique tumor target antigens, as well as improving CAR T cell trafficking to and expansion at the tumor site. This review focuses on combinatorial antigen targeting, regional delivery and approaches to improve CAR T cell persistence in the face of a hostile tumor microenvironment.